2011
DOI: 10.1002/path.2900
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical effects of T‐cadherin on squamous cell carcinoma: up‐ and down‐regulation increase xenograft growth by distinct mechanisms

Abstract: Mechanisms underlying cutaneous squamous cell carcinoma (SCC) tumour growth and invasion are incompletely understood. Our previous pathological and in vitro studies suggest that cell surface glycoprotein T-cadherin (T-cad) might be a controlling determinant of the behaviour of SCC. Here we used a murine xenograft model to determine whether T-cad modulates SCC tumour progression in vivo. Silencing or up-regulation of T-cad in A431 (shTcad or Tcad(+) , respectively) both resulted in increased tumour expansion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…As these cells give rise to transient amplifying cells and differentiated keratinocytes which move upward towards the skin surface to create new strata layers, T-cadherin expression decreases and is eventually completely lost. In skin tumours its expression level varies depending on tumour type and cell of origin: it is strongly expressed in basal cell carcinoma [55], but downregulated in squamous cell carcinoma and leads to increased tumour growth, invasion and metastasis [51,57,58], Together, these observations suggest that T-cadherin may be involved in coordination of epithelial differentiation and structural organisation of polarised tissues. Whilst the relationship between prostate cell types is still debated, lineage tracing studies [8][9][10] and the identification of cells with an intermediate phenotype (transit-amplifying cells) expressing both basal and luminal markers [59] support that basal cells serve as precursors for luminal cells.…”
Section: Discussionmentioning
confidence: 99%
“…As these cells give rise to transient amplifying cells and differentiated keratinocytes which move upward towards the skin surface to create new strata layers, T-cadherin expression decreases and is eventually completely lost. In skin tumours its expression level varies depending on tumour type and cell of origin: it is strongly expressed in basal cell carcinoma [55], but downregulated in squamous cell carcinoma and leads to increased tumour growth, invasion and metastasis [51,57,58], Together, these observations suggest that T-cadherin may be involved in coordination of epithelial differentiation and structural organisation of polarised tissues. Whilst the relationship between prostate cell types is still debated, lineage tracing studies [8][9][10] and the identification of cells with an intermediate phenotype (transit-amplifying cells) expressing both basal and luminal markers [59] support that basal cells serve as precursors for luminal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of T-cad expression in relation to histological classification of degree of differentiation revealed that T-cad loss in cutaneous SCC was not ubiquitous but occurred locally in association with histological features of a potentially more malignant and invasive phenotype (Pfaff et al, 2010). In vitro studies using HSC-1 or A431 SCC cell lines collectively demonstrated that T-cad silencing increased migratory, invasive, and proliferation potential, whereas the converse was true for T-cad overexpression (Mukoyama et al, 2005;Pfaff et al, 2010Pfaff et al, , 2011. However, in a murine xenograft model, either gain or loss of T-cad in A431 increased tumor expansion in vivo (Pfaff et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Down‐regulation of T‐cadherin in highly invasive hepatocellular carcinoma cells inhibited cell motility and did not influence proliferation (50). Silencing of T‐cadherin in cutaneous squamous cell carcinoma cells promoted the growth of tumor xenografts, but so did T‐cadherin overexpression through its ability to promote intratumoral angiogenesis (48).…”
Section: Discussionmentioning
confidence: 99%
“…Allelic loss of chromosome bands 16q24.1-q24.2, reduced expression of T-cadherin, and hypermethylation of the remaining allele have been detected in many human cancers including breast, colon, lung, hepatic, skin carcinomas, neuroblastoma, and others (9). Most studies showed that introduction of T-cadherin cDNA inhibited tumor cell growth, whereas T-cadherin silencing, conversely, stimulated proliferation, invasion, and metastasis in several in vitro and in vivo models (9,18,(47)(48)(49). Other data, however, show that T-cadherin does not obligatorily act as a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%